School burnout and cardiovascular functioning in young adult males: a hemodynamic perspective. (January 2014) - May, Ross W.; Sanchez-Gonzalez, Marcos A.; Brown, Preston C.; Koutnik, Andrew P.; Fincham, Frank D.
Abstract This study investigated aortic and brachial hemodynamic functioning that may link school burnout to cardiovascular risk factors. Methodological improvements from previous research were implemented including (1) statistical control of depressive and anxiety symptoms (2) resting, stress-induced and cardiac recovery condition comparisons and (3) use of pulse wave analysis. Forty undergraduate young adult males completed self-report measures of school burnout, trait anxiety and depressive symptoms. Participants then completed a protocol consisting of a 10-min seated rest, 5-min baseline (BASE), 3-min cold pressor test (CPT) and a 3-min recovery period (REC). Indices of brachial and aortic hemodynamics were obtained by means of pulse wave analysis via applanation tonometry. Controlling for anxiety and depressive symptoms, planned contrasts identified no differences in cardiovascular parameters at BASE between participants in burnout and non-burnout groups. However, negative changes in hemodynamic indices occurred in burnout participants at CPT and REC as evidenced by increased aortic and brachial systolic and diastolic blood pressures, increased left ventricular work and increased myocardial oxygen consumption. Findings suggest that school burnout symptoms are associated with cardiac hyperactivity during conditions of cardiac stress and recovery and therefore may be associated with the early manifestations of cardiovascular disease. Future studies are suggested to reveal underlying autonomic mechanisms explaining hemodynamics functioning in individuals with school burnout symptomatology.